Immunotherapeutic strategies for treating opioid use disorder and overdose. (2nd January 2023) - Luba, Rachel; Martinez, Suky; Jones, Jermaine; Pravetoni, Marco; Comer, Sandra D
ABSTRACT: Introduction: Development and implementation of effective treatments for opioid use disorder (OUD) and prevention of overdose are urgent public health needs. Though existing medications for OUD (MOUD) are effective, barriers to initiation and retention in treatment persist. Therefore, development of novel treatments, especially those may complement existing treatments, is needed. Areas covered: This review provides an overview of vaccines for substance use disorders (SUD) and mechanisms underlying their function and efficacy. Next, we focus on existing preclinical and clinical trials of SUD vaccines. We focus briefly on related strategies before providing an expert opinion on prior, current, and future work on vaccines for OUD. We included published findings from preclinical and clinical trials found on PubMed and ScienceDirect as well as ongoing or initiated trials listed on ClinicalTrials.gov. Expert opinion: The present opioid overdose and OUD crises necessitate urgent development and implementation of effective treatments, especially those that offer protection from overdose and can serve as adjuvants to existing medications. Promising preclinical trial results paired with careful efforts to develop vaccines that account for prior SUD vaccine shortcomings offer hope for current and future clinical trials of opioid vaccines. Clinical advantages of opioid vaccines appear to outnumber disadvantages, which may result in improved treatment options.